2023
DOI: 10.38151/akef.2023.50
|View full text |Cite
|
Sign up to set email alerts
|

Lone Wolf Personality, Career Adapt-Abilities, Proactive Career Behaviors, and Life Satisfaction: A Serial Mediation Analyses through the Career Construction Model of Adaptation

Abstract: The aim of the study is to test the Career Construction Model of Adaptation (CCMA) in university students (N = 406). 319 of (78.6%) the participants are female and 87 (21.4%) are male. The Lone Wolf Scale, The Turkish Five-Factor Short Form of the Career Adapt-Abilities Scale, The Career Engagement Scale, and The Satisfaction with Life Scale were used as measures. Hayes' models were used for mediation analyzes in the research model. It was tested a mediation model in which adaptive readiness (i.e., lone wolf p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…So, SME employees in Garut interact with each other between fellow employees for business development. The findings of this investigation are pertinent to work done by (Zalewska & Zwierzchowska, 2022), Dami et al, 2022;Mercader-Rubio et al, 2023;and Korkmaz & Brandt, 2023).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…So, SME employees in Garut interact with each other between fellow employees for business development. The findings of this investigation are pertinent to work done by (Zalewska & Zwierzchowska, 2022), Dami et al, 2022;Mercader-Rubio et al, 2023;and Korkmaz & Brandt, 2023).…”
Section: Discussionmentioning
confidence: 76%
“…The results showed that personality has a significant influence on life satisfaction (Zalewska & Zwierzchowska, 2022), and also confirmed that the big five personality has positive and negative influence on life satisfaction. Other studies have also revealed that personality has a significant effect on life satisfaction (Dami et al, 2022;Mercader-Rubio et al, 2023;Mercader-Rubio et al, 2023); and Korkmaz & Brandt, 2023). Supporting this explanation, the thesis Esteriyanah (2022) concluded that a person who works earnestly and feels happy with his job causes him to feel life satisfaction, and can happen on the contrary to feel dissatisfied with life because he is doing something wrong.…”
Section: The Influence Of Personality Toward Life Satisfactionmentioning
confidence: 92%